Complete plastome sequence of Vatica mangachapoi (Dipterocarpaceae): a vulnerable (VU) plant species in Southeast Asia - Jian-Hua Wang; Kun-Kun Zhao; Zhi-Xin Zhu; Hua-Feng Wang (Mitochondrial DNA. Part B. Resources, 2018)
Vatica mangachapoi is a tree up to 20 m tall with white resinous. It is distributed in China (Hainan province), Indonesia, Malaysia (N Borneo), Philippines, Thailand, and Vietnam. It grows in forests on hills and mountain slopes below 700 metres. Its durable wood is used for making boats and building bridges and houses. It has been ranked as a VU (Vulnerable) species in China. Here we report and characterize the complete plastid genome sequence of V. mangachapoi in an effort to provide genomic resources useful for promoting its conservation and phylogenetic research. The complete plastome is 151,538 bp in length and contains the typical structure and gene content of angiosperm plastome, including two Inverted Repeat (IR) regions of 23,921 bp, a Large Single-Copy (LSC) region of 83,587 bp and a Small Single-Copy (SSC) region of 20,109 bp. The plastome contains 114 genes, consisting of 80 unique protein-coding genes, 30 unique tRNA gene, and 4 unique rRNA genes. The overall A/T content in the plastome of V. mangachapoi is 62.80%. The phylogenetic analysis indicated that V. mangachapoi and V. odorata is closely related and as an independent branch in Malvales in our study. The complete plastome sequence of V. mangachapoi will provide a useful resource for the conservation genetics of this species and for the phylogenetic studies for Vatica.